Generation of a Tumor-Specific Chemokine Gradient Using Oncolytic Vesicular Stomatitis Virus Encoding CXCL9 - Elizabeth C. Eckert; Rebecca A. Nace; Jason M. Tonne; Laura Evgin; Richard G. Vile; Stephen J. Russell (Molecular Therapy: Oncolytics, 2020)
Genetically modified vesicular stomatitis virus (VSV) is an attractive agent for cancer treatment due to rapid intratumoral replication and observed clinical responses. Although VSV selectively kills malignant cells and can boost antitumor immunity, limited induction of intratumoral immune infiltration remains a barrier to efficacy in some cancer models. Here we engineered the oncolytic VSV platform to encode the T cell chemokine CXCL9, which is known to mediate the recruitment of activated CD8+ cytotoxic T cells and CD4+ T helper cells, and demonstrates conserved protein function between mice and humans. Chemotactic activity of the virally encoded chemokine was confirmed in vitro. Intratumoral concentration of CXCL9 was shown to increase after VSV therapy in three different cancer models, but to a much greater degree after VSV-CXCL9 therapy as compared with VSV control viruses. Despite a steep chemokine gradient from the tumor to the bloodstream, tumor trafficking of adoptively transferred and endogenous T cells was not measurably increased following VSV-CXCL9 therapy. Our results indicate that oncolytic VSV infection promotes release of CXCL9 in the tumor microenvironment, but further boosting of the functional chemokine gradient through virus engineering has little incremental impact on intratumoral immune cell infiltration in mouse and human tumor models. Keywords: oncolytic virotherapy, vesicular stomatitis virus, chemokine, chemokine gradient, CXCL9